Microcontroller Based Parking Lot Monitoring System Prototype - Heri Purwanto; Budi Prasetio (International Journal of Research and Applied Technology (INJURATECH), 2022)
Parking area is one of the facilities that must be available in specific or public places such as parks, recreation areas, malls, offices, business areas and agencies, and other places. Currently, the existing parking facilities generally do not provide information on the presence or absence of vacant parking spaces. This often causes problems in finding parking spaces, where vehicle users, especially four-wheeled vehicles (cars) will look for empty parking spaces by walking around so they can spend a lot of time. This study aims to create a parking lot monitoring system that is equipped with a microcontroller-based monitoring system so that vehicle users can find out how many parking spaces are available and where the parking lot is located. This parking monitoring system was developed using the prototyping method so that determining the need for the actual system is easier to realize. The test results of this device show that this prototype can provide information regarding the number of vacant parking lots and their locations. The impact of this research is that it can eliminate the accumulation of vehicles in front of the parking lot entrance, because vehicle users can easily and quickly find a parking location.